Hydrogel composites loaded with plant extract as an antibacterial and quorum sensing inhibiting wound dressing. - Baranda, Marivic Masangcay (2018.)
Delayed wound healing is often caused by bacterial infection. Furthermore, the persistent inflammation brought by the formation of biofilm via quorum sensing causes pain and discomfort. In a novel effort, this study fabricated an antibacterial and quorum sensing inhibiting hydrogel dressing loaded with plant extracts. KC-PVP hydrogel composites were loaded separately with 1 g/mL C. longa and H. durvillei extract under optimized conditions. The hydrogels were characterized through swelling test and FTIR analysis. It was determined that C. longa-loaded and H. durvillei¬-loaded hydrogels have a maximum swelling capacity of 175% and 135%, respectively. The antibacterial efficacy and the quorum sensing inhibition activity of extract-loaded hydrogels were evaluated using soft-layer agar well diffusion method. Hydrogel loaded with C. longa extract displayed 47.0 (±1.0), 45.0 (±1.0) and 32.33 (±0.58) mm mean growth inhibition against S. aureus, E. coli, and P. aeruginosa, respectively. H. durvillei extract-loaded hydrogels inhibited the growth of S. aureus, E. coli, and P. aeruginosa by 45.33 (±0.58). 43.67 (±1.52), and 33.33 (±0.58) mm in diameter, respectively. The quorum sensing inhibition zone of C. longa extract and H. durvillei extract-loaded hydrogels were 49.63 (±0.40) and 49.37 (±1.11) mm diameter, respectively. Overall, the extract-loaded hydrogel composites exhibited good antibacterial and quorum sensing inhibiting activity potentially for wound treatment.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2018.
Keywords: Quorum sensing; Antibacterial Activity; Hydrogel composites